Is plantar loading altered during repeated sprints on artificial turf in international football players? - Girard, O.; Millet, G. P.; Thomson, A.; Brocherie, F. (Journal of Sports Science & Medicine, 2018)
We compared fatigue-induced changes in plantar loading during the repeated anaerobic sprint test over two distinct distance intervals. Twelve international male football outfield players (Qatar Football Association) completed 6 × 35-m sprints (10 s of active recovery) on artificial turf with their football boots. Insole plantar pressure distribution was continuously recorded and values (whole foot and under 9 foot zones) subsequently averaged and compared over two distinct distance intervals (0-17.5 m vs. 17.5-35 m). Sprint times increased (p <0.001) from the first (4.87 ± 0.13 s) to the last (5.63 ± 0.31 s) repetition, independently of the distance interval. Contact area (150 ± 23 vs. 158 ± 19 cm2; -5.8 ± 9.1%; p = 0.032), maximum force (1910 ± 559 vs. 2211 ± 613 N; -16.9 ± 18.2%; p = 0.005) and mean pressure (154 ± 41 vs. 172 ± 37 kPa; -13.9 ± 19.0%; p = 0.033) for the whole foot were lower at 0-17.5 m vs. 17.5-35 m, irrespectively of sprint number. There were no main effects of sprint number or any significant interactions for any plantar variables of the whole foot. The distance interval × sprint number × foot region interaction on relative loads was not significant. Neither distance interval nor fatigue modified plantar pressure distribution patterns. Fatigue led to a decrement in sprint time but no significant change in plantar pressure distribution patterns across sprint repetitions.